International division of labor - Lim, Kean Fan (Wiley-Blackwell, 2015)
International division of labor refers to a conception of economic production as intrinsically transnational; of the interdependence between economic production and geographically-differentiated labor power in the first instance. ‘Old’ and ‘new’ versions of the concept abound: the ‘old’ international division refers to the Ricardian view that labor power enjoys comparative advantage based on finished products; the ‘new’ international division defines comparative advantages on the basis of tasks and processes. The new international division of labor was caused in large part by the crisis of Fordism, a process much researched by economic geographers. Empirical findings demonstrate a more complex process of transformation: the international division of labor was shaped by as much by changes in firm cultures and new politico-developmental objectives in developing countries as they were by the vertical distintegration in and relocation of production process by firms based originally in industrialized economies.